Does Gender Diversity Moderator The Nexus Between Board Characteristics And Financial Performance? - Shanak, Hosni Shareif Hussein (Migration Letters, 2024)
The study’s goal is to determine how board attributes like GEN, BSIZE, DUAL, and BI affect ROA for non-financial companies listed on the developing Palestine Stock Exchange (PSE) between 2016 and 2019. Multiple regression analysis was used to examine the relationship between board characteristics, gender diversity, and financial performance. Static panel data estimators with "pooled ordinary least squares (OLS), fixed effect, and random effect" were applied in this manner. Following a number of diagnostic tests, the OLS model was determined to be the best one. The findings demonstrate that DUAL and GEN have a strong and favorable connection with ROA. BSIZE and BI, however, have a favorable but negligible connection with ROA. More intriguingly, this study looks at how board characteristics and GEN interact to affect ROA. The most important finding is that GEN moderates the impact of board characteristic on ROA in a favorable way. The results of this study can alert responsible policymakers in developing nations, like Palestine, to innovative approaches that can result in better monitoring procedures and assist managers in boosting financial performance. For instance, businesses ought to be interested in having women on their board of directors.